Distinct features of fast oscillations in phasic and tonic rapid eye movement sleep - Brankačk, Jurij; Scheffzük, Claudia; Draguhn, Andreas (Journal of sleep research, 2012)
Spatiotemporal activity patterns of neurones are organized by different types of coherent network oscillations. Frequency content and cross-frequency coupling of cortical oscillations are strongly state-dependent, indicating that different patterns of wakefulness or sleep, respectively, support different cognitive or mnestic processes. It is therefore crucial to analyse specific sleep patterns with respect to their oscillations, including interaction between fast and slow rhythms. Here we report the oscillation profile of phasic rapid eye movement (REM), a form of REM sleep which has been implicated in hippocampus-dependent memory processing. In all analysed frequency bands (theta, gamma and fast gamma, respectively) we find higher frequencies and higher power in phasic REM compared to tonic REM or wakefulness. Theta-phase coupling of fast oscillations, however, was highest in tonic REM, followed by phasic REM and wakefulness. Our data suggest different roles of phasic and tonic REM for information processing or memory formation during sleep.